Further efforts to protect biodiversity in coastal waters of South Australia. (February 2015) - Kirkman, Hugh; Shepherd, Scoresby A.
Abstract: Marine sanctuary zones (MSZs) in South Australia were established under a regime of opposition from commercial and recreational fishers with some assistance from fisheries scientists. Fish exploitation was not the only threat discussed by the Scientific Working Group for Marine Protected Areas (MPAs) but it was considered as a major threat. There was some argument over the interpretation of the "Precautionary Principle" but one of the reasons for establishing a marine sanctuary zone is to conserve marine biological diversity not to manage fisheries. The genetic effects of overfishing fish and invertebrates can have a lasting effect on populations and the food web around them. Monitoring, evaluation and reporting are considered essential to management of MSZs' long-term strategy in terms of evaluating the efficacy of zoning arrangements and conservation outcomes. It is not certain that South Australia's system of MSZs will deliver their required outcome due to the compromises to science that had to be made. Highlights: Different applications of the Precautionary Principle are discussed. Threats to marine ecosystems. Genetic Consequences of Overfishing. Monitoring, Evaluation and Reporting for Sanctuary Zones. Ill-informed Opposition to MPAs.